Characterization of Tensile Strength and Degradation of Polymer Blend Reinforced with Black Carbone - Hafad, Sanaa A.; Hussin, Shemaa A.; Hmood, Abdalkalaq F.; Mahdi, Raghad R.; Shneen, Salam Waley (Journal of Fuzzy Systems and Control, 2024)
Samples of polymeric sheets of high-specification polycarbonate, which is characterized by high resistance in its pure form, were prepared and combined with low-density polyethylene sheets, which show low specifications relative to polycarbonate in equal proportions of (PC-%LDPE) (100%,80% 50%,20%). The preparation of the layered polymer mixtures was carried out using the micro-mixing method using an extruder. The effect of the binary polymer blends (PC-%LDPE) was demonstrated in increasing the maximum strength, and the effectiveness of advanced mechanical properties. The degradation of polymeric sets had little effect with the reinforcement of 20% of black carbon powder compared to other ratios.